2018
DOI: 10.1136/bmjopen-2017-021097
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of childhood sleep-disordered breathing (SDB) in Beijing: validation of survey methodology

Abstract: ObjectiveTo systematically investigate and validate the survey methodology for the epidemiological study of childhood sleep-disordered breathing (SDB) in mainland China using the Mandarin version of the Pediatric Sleep Questionnaire-Sleep-Related Breathing Disorder (PSQ-SRBD).DesignA cross-sectional study using randomised, stratified, multistage, cluster sampling method.SettingA total of 11 kindergartens, 7 primary schools and 8 middle schools from 7 districts of Beijing, China.ParticipantsA total of 9198 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The PSQ was used to assess the scale of SRBD. The PSQ identifies children with SRBD with a sensitivity of 83% and a specificity of 87%; its applicability and generalizability in assessing childhood SRBD in China has been confirmed [ 24 ]. This multipage questionnaire consists of 22 questions on snoring, sleepiness, and behavioral problems and has been used frequently for sleep-associated respiratory research studies [ 15 , 16 , 24 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSQ was used to assess the scale of SRBD. The PSQ identifies children with SRBD with a sensitivity of 83% and a specificity of 87%; its applicability and generalizability in assessing childhood SRBD in China has been confirmed [ 24 ]. This multipage questionnaire consists of 22 questions on snoring, sleepiness, and behavioral problems and has been used frequently for sleep-associated respiratory research studies [ 15 , 16 , 24 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The PSQ identifies children with SRBD with a sensitivity of 83% and a specificity of 87%; its applicability and generalizability in assessing childhood SRBD in China has been confirmed [ 24 ]. This multipage questionnaire consists of 22 questions on snoring, sleepiness, and behavioral problems and has been used frequently for sleep-associated respiratory research studies [ 15 , 16 , 24 31 ]. The three possible responses to each question are “yes = 1,” “no = 0,” and “do not know = missing.” The number of symptom items endorsed positively (“yes”) is divided by the number of items answered positively or negatively; the denominator therefore excludes items with missing responses, i.e., items answered with “do not know.” Scores >0.33 are considered positive and suggestive of a high risk of having SRBD.…”
Section: Methodsmentioning
confidence: 99%
“…The Paediatric Sleep Questionnaire (PSQ), developed by Chervin et al [17], has a low cost and a precise cut-off score (> 0.33), and identifies children with OSAS with a sensitivity of 83% and a specificity of 87%. Li et al confirmed that the PSQ was a successful methodology for the investigation of childhood SDB in Beijing, China, thereby supporting the applicability and generalizability of the PSQ in a large epidemiological survey of childhood SDB in China [18].…”
Section: Introductionmentioning
confidence: 91%
“…The respondents were recruited from 9 kindergartens, 10 primary schools, and 9 middle schools, and encompassed children aged 3-14 years. Base on the sample size of each group and school scale, the selection of the school and each grade among the same educational institutions was based on computer-generated random numbers [18].…”
Section: Setting Sampling and Participantsmentioning
confidence: 99%
See 1 more Smart Citation